2018
DOI: 10.1371/journal.pone.0201258
|View full text |Cite
|
Sign up to set email alerts
|

To be funny or not to be funny: Gender differences in student perceptions of instructor humor in college science courses

Abstract: For over 50 years instructor humor has been recognized as a way to positively impact student cognitive and affective learning. However, no study has explored humor exclusively in the context of college science courses, which have the reputation of being difficult and boring. The majority of studies that explore humor have assumed that students perceive instructor humor to be funny, yet students likely perceive some instructor humor as unfunny or offensive. Further, evidence suggests that women perceive certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 51 publications
(57 reference statements)
0
46
0
Order By: Relevance
“…While humor can lead to an array of positive outcomes for students, they likely have to perceive the humor to be funny in order for it to be effective. In fact, a recent study we conducted across 25 college science courses demonstrated that while funny humor enhanced students' sense of belonging, attention to course content, and relationships with the instructor, offensive humor decreased students' sense of belonging, attention to course content, and relationships with the instructor (6). Importantly, humor is subjective and jokes that one person may find funny, someone else may find offensive.…”
Section: An Example Of [One Of] His Pun[s] Included a Picture Of A Goatmentioning
confidence: 95%
See 4 more Smart Citations
“…While humor can lead to an array of positive outcomes for students, they likely have to perceive the humor to be funny in order for it to be effective. In fact, a recent study we conducted across 25 college science courses demonstrated that while funny humor enhanced students' sense of belonging, attention to course content, and relationships with the instructor, offensive humor decreased students' sense of belonging, attention to course content, and relationships with the instructor (6). Importantly, humor is subjective and jokes that one person may find funny, someone else may find offensive.…”
Section: An Example Of [One Of] His Pun[s] Included a Picture Of A Goatmentioning
confidence: 95%
“…Humor can be a powerful tool that science instructors can use to connect with students, build classroom community, and create a more engaging classroom (1)(2)(3)(4)(5). Studies have shown that humor can help increase instructor immediacy, narrowing the psychological distance between students and instructors, and help students perceive instruc-tors as more relatable (6)(7)(8). Science instructors have been previously described as uninteresting and unfriendly (9)(10)(11)(12)(13), so humor is one method by which they can seem more like a "real person" (6).…”
Section: An Example Of [One Of] His Pun[s] Included a Picture Of A Goatmentioning
confidence: 99%
See 3 more Smart Citations